The Use of Factual Reading in English Writing - Farahdiba, Syarifah; Fitriyani, Fitriyani (Universitas Negeri Makassar, 2013)
The study is aimed at finding out and describing the students’ improvement in writing an English composition and their attitude toward the use of factual readings as learning media. The study used quasi-experimental method with one experimental and one control classes. It was found that that there is a writing improvement of students in experiment group through the use of factual Reading with 18.72 higher. The result of t-test value shows that the improvement of students’ writing skill before and after given factual readings in writing practices is significantly reliable. Thus, it can be concluded that the use of factual Reading can help improving students’ writing skill